The prevalence of anti-sperm antibodies in cattle in the Eastern Anatolian Region of Turkey - Risvanli, A; Aydin, M; Kaygusuzoglu, E; Bulut, H; Apaydin, AM; Bolat, Y (Biomed Central Ltd, 2003)
Sera from 200 cows and heifers of different breeds were subjected to an enzyme immunoassay (EIA) for anti-sperm antibodies. Fifteen (7.5%) of the animals tested were positive for the antibodies. The prevalence of the antibodies was greatest amongst the cows that had had three or more inseminations: six (17.65%) of 34 cows tested positive.
Keywords: cattle; anti-sperm antibody; Turkey